Determination of the REE content, geological age, and absorbed alpha dose of allanite mineral from Palawan, Philippines. (27th March 2019) - Dingle, Cheri Anne M.; Jecong, Julius Federico M.; Hila, Frederick C.; Ramo, Ma. Elina Salvacion V.; Guillermo, Neil Raymund D.; Vasquez Jr, Magdaleno R.; Samson, Vallerie Ann I.
Abstract : Allanite is a common accessory mineral in igneous rocks that contains significant amounts of rare‐earth elements (REEs), thorium (Th), and uranium (U). The presence of Th and U in the allanite exposes it to radiation resulting in radiation damage in its crystal structure and further leads to metamictization. Hence, allanite can be used as a natural analogue to assess the long‐term radiation effects in materials for high‐level nuclear waste disposal. It provides information on the effect of α‐decay on the crystal structure including the stability and integrity of the material. In this study, the absorbed α‐dose of allanite from Ombo, Palawan, Philippines, was estimated from the Th and U content and geological age of the mineral using X‐ray fluorescence and gamma‐ray spectrometry. The amount of Th and REE was measured to be around 1.37 and 30.4 wt.%, respectively. Radiometric dating using gamma‐ray spectrometry estimated the age of the allanite mineral to be around 24–35 million years. Having obtained the amount of radioactivity and the time of exposure, the corresponding absorbed α‐dose was estimated to be at 2.84 × 10 14 α‐decays/mg. Results suggest that the allanite mineral studied has not accumulated significant radiation damage to cause amorphization and still exhibit a crystalline structure. This study may provide data on the properties of allanite or silicate matrices as part of the ongoing studies on silicate minerals as natural analogues.